Pengembangan Instrumen Penilaian Higher Order Thinking Skills (HOTS) Pada Materi Asam Basa SMA/MA Kelas XI - Nunung Ratna Ningsih; Agus Kamaludin (Postgraduate, University of Mataram, 2023)
Higher Order Thinking Skills (HOTS) are necessary skills to deal with the 21st century. This research aimed to develop a HOTS-based assessment instrument on acid-base for class XI that meets the aspects of validity, reliability, difficulty level and distinguishing power. This research is a Research and Development (R&D) study with a 4D model. The quality of the product was assessed by one material expert lecturer, one media expert lecturer, and four chemistry teachers of high school and tested on 30 science students in eleventh grade. The assessment of product quality obtained from material experts is 97.67% with the Very Good (VG) category; from media expert, it was 97.44% with the Very Good (VG) category; according to chemistry teachers, all items are feasible to be used as a field trial. After conducting the field trial, the product contained 18 valid items and 2 invalid items with the very reliable category, which was 0.899. At the difficulty level, the product had 11 easy items and 9 medium items. At the level of distinguishing power, the product had 1 very bad item, 2 sufficient items, 9 good items, and 8 very good items. Therefore, the resulting assessment questions instrument can be used to measure students' HOTS knowledge